Serum Magnesium Concentration Is Inversely Associated with Albuminuria and Retinopathy among Patients with Diabetes - Jun Lu; Yuying Gu; Meixiang Guo; Peihong Chen; Hongtao Wang; Xuemei Yu (Journal of Diabetes Research)
Aim. To investigate the association between serum magnesium levels and microvascular complications among patients with diabetes. Methods. Patients with diabetes were recruited between April 2012 and January 2015. All patients received an assay of serum magnesium concentration, were screened for 24 h albumin excretion rate, and underwent nonmydriatic fundus photography. Albuminuria and retinopathy were defined accordingly. A total of 3,100 patients with normal serum magnesium levels were included in this study. Results. Patients with albuminuria and/or retinopathy had lower levels of serum magnesium than patients without these complications (P<0.001). The prevalence of isolated albuminuria, isolated retinopathy, and combined albuminuria and retinopathy decreased as the concentration of serum magnesium increased. Multiple logistic regression analysis indicated that the odds ratio for isolated albuminuria, isolated retinopathy, and concomitant albuminuria and retinopathy decreased by approximately 20% for every 0.1 mmol/L increase in serum magnesium concentration. Conclusion. Serum magnesium levels were negatively associated with the risk of diabetic microvascular complications among patients with serum magnesium levels within the normal range.